Pengembangan Media Pembelajaran E-Fotonovela Fisika Menggunakan Android Berbasis Karakter untuk Siswa Tuna Rungu ( SLB – B ) - Imas Ratna Ermawati; Andita Andita; Aisyah Fitriana; Andryastuti Andryastuti; Hani R (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2020)
This study aims to develop E-fotonovela media for deaf students in SMLB-B. The research method used is the Research and Development (R & D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of the study were deaf students of high school level (SMLB-B), which were conducted in two schools namely SLB N 6 Jakarta and SLB N 7 Jakarta. Research and development produces E-fotonovela media in the form of books with Android-assisted, magnetic materials that are suitable for use based on an average expert judgment of 98% with very good criteria. The assessment of the effectiveness of the media obtained a percentage of 94% with very good criteria, and based on the effectiveness of learning outcomes obtained a value of 74.5% good criteria, which means that the photonovela media on magnetic material is suitable for use as a learning medium in SMAL-B (deaf). While the characters obtained after using E-fotonovela with the thunkecable android application are shown by the overall average score for the 6 principle characters of users at a high level of honest average = 8,189; average discipline = 7.834; average curiosity = 6,545; creative average = 8.037; average cooperation = 8,500 and average responsibility = 8,310.